RESILIENCE AND ADAPTATION: THE ECONOMY OF PESANTREN AMIDST CAPITALISM - Husnul Amin (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
In the capitalist era, modernizing pesantren administration is crucial for sustainability and growth. By implementing strategic management methodologies and technological advancements, pesantrens can ensure operational efficiency and sustainability. Consultant participation can provide significant leadership in progress and development. Pesantren's educational system must undergo evolution, incorporating curriculum modifications, leadership development, and efficient supervision. Modern pesantren administrations adapt their leadership, curricula, instructional methodologies, administrative frameworks, and educational systems to align with capitalism's ideals. Community participation is essential for bottom-up strategy, fostering collective responsibility and solidarity. Capitalism influences political leadership by prioritizing development to address societal transformations and enhancing human resource quality through community-government collaborations. Pesantren enrollment is not directly influenced by capitalism, as Islamic boarding schools focus on spiritual growth and Islamic knowledge. To achieve Society 5.0 goals, modern pesantren organizations must update by deliberate, creative, targeted, accepted, and objective reforms that efficiently use information and technology.